A CLASSICAL MODEL OF EDUCATION, GROWTH, AND DISTRIBUTION. (July 2020) - Dutt, Amitava Krishna; Veneziani, Roberto
Abstract : We develop a classical macroeconomic model to examine the growth and distributional consequences of education. Contrary to the received wisdom, we show that human capital accumulation is not necessarily growth-inducing and inequality-reducing. Expansive education policies may foster growth and reduce earning inequalities between workers, but only by transferring income from workers to capitalists. Further, the overall effect of an increase in education depends on the actual characteristics of the educational system and on the nature of labor market relations. Although the primary aim of the paper is theoretical, we argue that the model identifies some causal mechanisms that can contribute to shed light on recent stylized facts on growth, distribution, and education for the USA.